THE HISTORY OF CIVILIZATIONS OF PRE-COLUMBIAN AMERICA: ASSESSMENT OF 7-8 GRADE WORLD HISTORY TEXTBOOKS FOR UKRAINIAN STUDENTS - Mereniuk, Khrystyna; Parshyn, Illia (Revista Prâksis, 2025)
The study of the civilisations of pre-Columbian America opens up a diverse world of ancient cultures, their achievements and heritage to the modern student. The purpose of the study is to analyse the state of coverage of the history of medieval and early modern South American indigenous peoples in Ukrainian school history textbooks. For the content analysis, 6 textbooks on the world history of Ukraine were selected. We also selected 2 textbooks for the integrated course, which will be used by 7th grade students. The textbooks were selected based on the indicator of teacher choice – the minimum number of 18 thousand copies per country. The introduction to the study begins with the fact that Pre-Columbian history is a terra incognita in the worldview of Ukrainian schoolchildren. However, as it turned out, some modern textbooks describe in detail the history of Pre-Columbian civilisations, their way of life, culture, social system, and even military art. Taking into account the specifics of these textbooks, they are generally written in clear and accessible language for children of grades 7 and 8. It has been established that in some textbooks this topic is not sufficiently visualised in an integrative way. An important drawback is that most 2021 textbooks make little or no mention of other peoples and civilisations of Pre-Columbian America. The exception is the integrated textbook for 2024, in which the social, economic, cultural and political development of the Pre-Columbian civilisations is presented in more depth.